Corporate Action : Apakah Memberi Dampak Pada Likuiditas Saham? - Saputri, Anisa Herwi; Sari, Herlinda Maya Kumala; Prapanca, Detak (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
This study aims to provided understanding, knowledge, and testing of the impact of corporate actions in the form of stock splits, rights issues, and acquisitions on stock liquidity in companies included in the LQ45 stock index for the period 2020 - 2022. From a population of 60 companies that are members of the LQ45 stock index during 2020-2022, the sample selected using the purposive sampling method is 38 companies. The analysis method in this study uses a paired t-test with observations 5 days before and after corporate action. Statistical analysis using the Wilcoxon Signed Rank Test and processed using SPSS 25. The results of this study indicate that stock splits can significantly affect stock liquidity, while rights issues and acquisitions do not significantly affect stock liquidity.